2000
DOI: 10.1046/j.1360-0443.2000.95694911.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical education in substance‐related disorders: components and outcome

Abstract: There is growing consensus in the selection of a combined didactic and interactive educational strategy but few empirical data as to the more cost-effective learning interventions. Training must be reinforced at regular intervals. While the expanding panoply of interventions available to physicians should enhance the perceptions of role legitimacy and treatment optimism, cohort studies across levels of education, specialty groups and across-substance and other addictive behaviors are required to determine cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 0 publications
3
58
0
2
Order By: Relevance
“…Research on medical education has shown that training can be effective in improving students' and physicians' knowledge and skills in addressing alcohol issues (106,(116)(117)(118), but changes in knowledge may be easier to produce than changes in attitudes and behavior (119). A review of the components and outcomes of medical education in substancerelated disorders concluded that the selection of a combined didactic and interactive educational strategy may be the most cost-effective learning strategy, but there is little empirical evidence to support this approach (119).…”
Section: Brief Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on medical education has shown that training can be effective in improving students' and physicians' knowledge and skills in addressing alcohol issues (106,(116)(117)(118), but changes in knowledge may be easier to produce than changes in attitudes and behavior (119). A review of the components and outcomes of medical education in substancerelated disorders concluded that the selection of a combined didactic and interactive educational strategy may be the most cost-effective learning strategy, but there is little empirical evidence to support this approach (119).…”
Section: Brief Treatmentmentioning
confidence: 99%
“…Barriers to adequate coverage of alcohol and drug-related problems in both medical schools and continuing professional education include traditional attitudes about the moral culpability of chronic alcoholics, confusion as to whether problem drinking is a medical or psychiatric concern, lack of faculty role models, lack of training materials, and role ambiguity regarding who is responsible for screening and intervention (114,115). Research on medical education has shown that training can be effective in improving students' and physicians' knowledge and skills in addressing alcohol issues (106,(116)(117)(118), but changes in knowledge may be easier to produce than changes in attitudes and behavior (119). A review of the components and outcomes of medical education in substancerelated disorders concluded that the selection of a combined didactic and interactive educational strategy may be the most cost-effective learning strategy, but there is little empirical evidence to support this approach (119).…”
Section: Brief Treatmentmentioning
confidence: 99%
“…A recent review of the components and outcomes of medical education in substance-related disorders concluded that the selection of a combined didactic and interactive educational strategy may be the most cost-effective learning strategy, but there is little empirical evidence to support this approach (24).…”
Section: Introductionmentioning
confidence: 99%
“…Research on medical education has shown that training can be effective in improving students' and physicians' knowledge and skills in addressing alcohol issues (21)(22)(23), but changes in knowledge may be easier to produce than changes in attitudes and behavior (24). A recent review of the components and outcomes of medical education in substance-related disorders concluded that the selection of a combined didactic and interactive educational strategy may be the most cost-effective learning strategy, but there is little empirical evidence to support this approach (24).…”
Section: Introductionmentioning
confidence: 99%
“…Entretando, ainda que as atitudes profissionais de saúde relacionadas às pessoas com problemas de uso e abuso de álcool tendam a refletir na sociedade, pois inquéritos realizados nos EUA, Austrália e Reino Unido têm encontrado que as atitudes dos profissionais de saúde são geralmente negativas (Eliason, Gerken, 1999;El-Guebaly et al, 2000;Happell, Taylor, 2001). Assim, é importante ressaltar que, para a mudança de atitude de um individuo, não basta apenas o conhecimento, mas também que haja uma adequação de papel, um papel de legitimidade e suporte (Shaw et al, 1978).…”
Section: Associação Entre As Variáveis Sociodemográficas E As Atitudeunclassified